PENINGKATAN NILAI TAMBAH BAMBU MELALUI PENERAPAN TEKNOLOGI PENGOLAHAN BAMBU DI DESA LEGOK KECAMATAN BANTARKAWUNG KABUPATEN BREBES - Laksmi Indyastuti, Devani; lestari, Sri; Sudibyo, Gatot Heri; Fitriana, Gita Fadila (Jurnal Abdi Insani, 2024)
The problem faced in Legok Village in general is the large number of Poor Family Heads. Village monograph data in 2023 shows that out of 824 families, 54.85% of them (452 ​​families) are poor families. This village has very large bamboo plant potential, but it has not been managed properly. In this village there is a Bamboo Farmer group "Tunas Karya Lestari" and a Bamboo Craftsman group "Berkah Bambu Lestari" but they have not been empowered optimally. This poverty problem can be overcome by increasing community income through efforts to make Legok Village a bamboo-based business center from upstream to downstream in accordance with the potential of this village. The purpose of this activity is to develop bamboo products in Legok Village by overcoming the problems in it. The method of activity is to conduct bamboo cultivation development training and training in making unique bamboo products that are suitable for marketing. The results of the activity are bamboo material preservation training, bamboo pest control training, financial management training, administrative management, product manufacturing capabilities that increase selling prices and markets. The result of the training is the readiness and creation of bamboo product producers who are able to produce quality products, effectively and efficiently, and are able to increase sales of bamboo products.   Keywords: Bamboo Products, Legok Village, Quality Products, Effective, Efficient